JURIDICAL ANALYSIS OF REGULATION NO. 15 OF 2020 CONCERNING THE TERMINATION OF PROSECUTION IN CRIMINAL OFFENSES IN THE PERSPECTIVE OF THE CRIMINAL JUSTICE SYSTEM IN INDONESIA - Aziz, Sultan Abdul; Sugilang, Sugilang; Prasetyo, Wahyu Wibowo; Asmara, Teddy; Harliyanto, Rois (Al-Makki Publisher, 2024)
The purpose of this study is to analyze: first, the study of Attorney General Regulation No. 15 of 2020 concerning the termination of prosecution based on restorative justice in the perspective of the criminal justice system in Indonesia. Second, the mechanism for terminating prosecution based on restorative justice based on Attorney General Regulation No. 15 of 2020 has fulfilled the requirements and objectives. This legal research uses a normative juridical approach method. The results of the study concluded that there is a contradiction between the position of Perja No. 15 of 2020 and the justice system in Indonesia. First, it shows that the findings in article 2 of Perja no 15 of 2020